MYB gene family in the diatom Phaeodactylum tricornutum revealing their potential functions in the adaption to nitrogen deficiency and diurnal cycle. Issue 1 (26th November 2021) - Wang, Wanna; Fang, Hao; Aslam, Muhammad; Du, Hong; Chen, Jichen; Luo, Haodong; Chen, Weizhou; Liu, Xiaojuan
Abstract : The MYB transcription factor (TF) family is one of the largest and most important TF families, regulating the growth and response of microalgae to stress. However, the gene structure and characteristics of Phaeodactylum tricornutum MYB TFs, and their functions under nitrogen deficiency, have not been explored yet. To identify all P. tricornutum MYB (PtMYB) genes, the MYB gene family was analyzed at the genome‐wide level in this study. A total ofm26 PtMYB genes were identified from the genome of P. tricornutum . These PtMYB genes were divided into 5 subfamilies: 5R‐MYB, 4R‐MYB, R2R3‐MYB, R1R2R3‐MYB, and MYB‐related proteins. Phylogenetical motif and gene structure analyses of MYB genes indicated that the number and proportion of MYB TFs were species‐specific, and MYB genes exhibited a lot of duplication events from microalgae to higher plants. Furthermore, the differentially expressed patterns of all 26 PtMYB TFs implied that PtMYB genes might have functional specificity under nitrogen deficiency. Homology analysis of MYB genes revealed that PtMYB3, PtMYB15, and PtMYB21 might play important roles in the regulation of the diurnal cycle and response to nitrogen stress in P. tricornutum . PtMYB3, PtMYB15, and PtMYB21 genes might be used as potential candidate genes for further studying the regulatory mechanisms of P. tricornutum under nitrogen deficiency. This work provides an important foundation for the future research of the potential functions of PtMYB genes and its diurnal regulatory mechanisms under nitrogen deficiency.